The international penetration of ibusiness firms: Network effects, liabilities of outsidership and country clout - Chen, Liang; Shaheer, Noman; Yi, Jingtao; Li, Sali (Journal of International Business Studies, 2019)
The burgeoning of ibusiness firms in the modern digital economy challenges the received internationalization theory. Given that ibusinesses such as social networking sites create value by providing a digital platform for users to interact with one another, we employ a user-network perspective and externalization logic, suggesting that ibusinesses’ internationalization process depends critically on users’ collective interactions, instead of being solely driven by firms’ market commitments, as noted by the Uppsala model. However, ibusinesses may suffer from liabilities of outsidership due to the boundedness of international network effects. Drawing on social network theory, we demonstrate that such liabilities can be mitigated by first diffusing the ibusiness platform in countries with higher clout. Our analysis using a unique dataset of mobile ibusiness platforms finds empirical support for the hypotheses. We discuss theoretical implications for the network approach of the Uppsala model in the digital era.